A visual analogue scale companion for the six‐item Hamilton Depression Rating Scale. (23rd July 2019) - May, Tamara; Pridmore, Saxby
Abstract: Objective: The six‐item Hamilton Depression Rating Scale (HAMD6) is a clinician rated measure which lacks a self‐report companion. We explored whether a six‐item client rated visual analogue scale (VAS6) based on the HAMD6, was a consistent and valid measure of depression and useful for clinical practice. Method: Participants were N = 117 participants, 88 (75%) female, with major depressive disorder (MDD) who received transcranial magnetic stimulation (TMS). Pre‐ and post‐treatment a trained clinician completed the HAMD6 and Clinical Global Impression Scale for Severity (CGI‐S), and patients the self‐reported VAS6. Results: VAS6 internal consistency using Cronbach's alpha was 0.87. VAS6‐HAMD6/GGI‐S spearman correlations were moderate‐strong for four items (depressed mood; work/activities; feelings of guilt; anxiety) and the total score and weak for two items (somatic symptoms, retardation). Conclusions: The self‐reported VAS6 was a valid measure of core aspects of depression measured by the HAMD6. It is cost effective (takes relatively little clinician time) and is a useful companion to the clinician reported HAMD6.